2013
DOI: 10.1186/1471-2202-14-100
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent persistent expression of zif268during rest is preserved in the aged dentate gyrus

Abstract: BackgroundAging is typically accompanied by memory decline and changes in hippocampal function. Among these changes is a decline in the activity of the dentate gyrus (DG) during behavior. Lasting memory, however, is thought to also require recapitulation of recent memory traces during subsequent rest – a phenomenon, termed memory trace reactivation, which is compromised in hippocampal CA1 with progressive age. This process has yet to be assessed in the aged DG, despite its prominent role in age-related memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
5
12
0
Order By: Relevance
“…In particular, based on human neuroimaging data linking CA3/DG activity to accuracy in distinguishing highly similar visual stimuli (Kirwan and Stark, 2007;Bakker et al, 2008;Yassa and Stark, 2011;Reagh and Yassa, 2014;Reagh et al, 2018), we sought to determine if disrupting neural activity in the rodent CA3/DG with intrahippocampal infusions of muscimol would selectively impair discrimination of a target object from highly similar lure objects. However, in verifying the effects of muscimol on neural activity, we discovered infusion of this GABAA agonist at the coordinates used here produced excitation throughout the DG granule cell layer (Fig.1C), which typically shows sparse levels of activation assessed with the same methods (Small et al, 2004;Marrone et al, 2011Marrone et al, , 2012Penner et al, 2011;Gheidi et al, 2013). A subsequent experiment confirmed that, relative to vehicle, muscimol infusions robustly increased expression of the activity-dependent immediate-early genes Arc and Homer1a in DG (Fig.3).…”
Section: Discussionsupporting
confidence: 56%
“…In particular, based on human neuroimaging data linking CA3/DG activity to accuracy in distinguishing highly similar visual stimuli (Kirwan and Stark, 2007;Bakker et al, 2008;Yassa and Stark, 2011;Reagh and Yassa, 2014;Reagh et al, 2018), we sought to determine if disrupting neural activity in the rodent CA3/DG with intrahippocampal infusions of muscimol would selectively impair discrimination of a target object from highly similar lure objects. However, in verifying the effects of muscimol on neural activity, we discovered infusion of this GABAA agonist at the coordinates used here produced excitation throughout the DG granule cell layer (Fig.1C), which typically shows sparse levels of activation assessed with the same methods (Small et al, 2004;Marrone et al, 2011Marrone et al, , 2012Penner et al, 2011;Gheidi et al, 2013). A subsequent experiment confirmed that, relative to vehicle, muscimol infusions robustly increased expression of the activity-dependent immediate-early genes Arc and Homer1a in DG (Fig.3).…”
Section: Discussionsupporting
confidence: 56%
“…Although post-hoc analyses indicate that aged animals took significantly longer than both middle-aged and young animals to reach the visible platform on day 1 (p = 0.01), much smaller differences in the average distance swam to reach the platform were observed on day 2. Consistent with this observation, post-hoc tests showed no significant difference was observed in the distance travelled between aged and middle-aged rats, consistent with previous reports [ 7 , 29 , 30 , 33 ], nor between middle-aged and young rats. A significant difference remained between young and aged rats (p = 0.04).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, our c-Fos mRNA positive cell quantification revealed that the number of cells activated in response to both tone and home cage far exceeded that expected by random chance. This may reflect ‘replay’ of the previous experience with tone, as has been previously reported with both in vivo electrophysiology in freely moving rats (Wilson & McNaughton, 1994) and IEG detection methods in animals during spatial navigation (Gheidi, Azzopardi, Adams, & Marrone, 2013). The finding lends support to the notion that “background” IEG expression is not mere random activity and may represent mnemonic replay of previous experiences.…”
Section: Discussionsupporting
confidence: 58%